2022
DOI: 10.1177/03000605211039480
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ITGAX and CCR1 as potential biomarkers of atherosclerosis via Gene Set Enrichment Analysis

Abstract: Objective Atherosclerosis (AS) is a life-threatening disease in aging populations worldwide. However, the molecular and gene regulation mechanisms of AS are still unclear. This study aimed to identify gene expression differences between atheroma plaques and normal tissues in humans. Methods The expression profiling dataset GSE43292 was obtained from the Gene Expression Omnibus (GEO) dataset. The differentially expressed genes (DEGs) were identified between the atheroma plaques and normal tissues via GEO2R, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While the AQP series is closely related to autoimmune diseases such as optic neuromyelitis optica, dry syndrome, and rheumatoid arthritis, SLE is an autoimmune disease with few studies related to AQP9 and SLE, and the correlation between AQP9 and SLE could be considered in future studies to provide new targets for the clinical treatment of SLE. Shen et al 16 found, through a comprehensive bioinformatics study, that CCR1 expression was significantly higher in atherosclerotic plaque samples than in healthy samples 16 and a study confirmed that the use of pharmacological antagonists of CCR1 reduces the risk of cardiovascular disease. 17 Other studies have shown that CCR1 is upregulated in the skin of SLE patients, which leads to SLE skin tissue damage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While the AQP series is closely related to autoimmune diseases such as optic neuromyelitis optica, dry syndrome, and rheumatoid arthritis, SLE is an autoimmune disease with few studies related to AQP9 and SLE, and the correlation between AQP9 and SLE could be considered in future studies to provide new targets for the clinical treatment of SLE. Shen et al 16 found, through a comprehensive bioinformatics study, that CCR1 expression was significantly higher in atherosclerotic plaque samples than in healthy samples 16 and a study confirmed that the use of pharmacological antagonists of CCR1 reduces the risk of cardiovascular disease. 17 Other studies have shown that CCR1 is upregulated in the skin of SLE patients, which leads to SLE skin tissue damage.…”
Section: Discussionmentioning
confidence: 94%
“…18 IL1RN is an endogenous natural antagonist of IL-1 and usually acts by competing for the binding site of IL-1R with IL-1. 19 Yan et al 16 determined that IL1RN was upregulated in AS tissues by bioinformatics methods and further verified its expression level was significantly higher than that of the control group by experiments. Similarly, a correlation meta-analysis showed that genetic polymorphisms in IL1RN are strongly associated with susceptibility to SLE, 20 however, additional research is required to determine how these polymorphisms contribute to the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 96%
“…ITGAX is involved in early AS lesion formation and is highly expressed in AS tissues, and several bioinformatic analyses have suggested it as a potential biomarker for AS 34 , 35 . The mice with double knockouts of ITGAX and Apoe demonstrated lower monocyte adhesion and AS plaque macrophage content 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include immune system [54], metabolism of lipids [55], phospholipid metabolism [56] and disease [57] plays an important role in CAD. DOCK4 [58], CEACAM1 [59], STAT1 [60], ARG1 [61], TLR4 [62], ADAM9 [63], VNN1 [64], ABCA1 [65], STAT2 [66], TLR5 [67], PTGS2 [68], RNF213 [69], ZDHHC17 [70], JAK2 [71], TLR8 [72], NOTCH2 [73], PDGFC (platelet derived growth factor C) [74], CMPK2 [75], TLR2 [76], CYP1B1 [77], CCR1 [78], HDAC9 [79], IL1RN [80], GCH1 [81], LYST (lysosomal trafficking regulator) [82], PELI1 [83], EGR1 [84], SNX10 [85], CA2 [86], ZEB2 [87], HIF1A [88], PLA2G7 [89], CCR2 [90], GAB1 [91], IRAK3 [92], LDLR (low density lipoprotein receptor) [93], TLR6 [94], SIRT1 [95], NOD2 [96], ATP10D [97], ELOVL6 [98], VCAN (versican) [99], TET2 [100], TET3 [101], ZBTB20 [102], HS3ST1 [103], PF4 [104], DNAJC2 [105], NFIA (nuclear factor I A) [106], CCR7 [107], PRDX2 [108], ADK (adenosine kinase) [109], TCF7 [110], LGALS3 [111], OLFM2 [112], HDAC11 [113] and ARPC1B [114] are significantly related to the atherosclerosis. Studies have revealed that KCNJ2 [115], TLR4 [116], JAK2 [117], TLR2 [118], EGR1 [119], GAB1 [120], ZBTB11 [121], BIN1 [122], TCF4 [123], PPP1R13L [124], TRPM4 [125], LGALS3 [126] and SNTA1 [127] plays a key role in cardiac arrhythmia.…”
Section: Discussionmentioning
confidence: 99%